(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the role and importance of a number of factors in the formation of the national and legal culture of young people and their upbringing in the spirit of the national ideal is highlighted based on analytical opinions.